Muslim Women’s Roles in Early Childhood Education - Munirah, Munirah (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The role of Muslim women in early childhood education is very urgent in education because women are the first source of knowledge for children. There are many supporting and inhibiting factors for the role of Muslim women executors. This study aims to find the role of female educators in Islam as a dual function that functions as a teacher, parent, and community member. The research method uses qualitative with a phenomenological approach. The findings show the role of Muslim women is not ideal, including the role of women as educators in schools, parents, and education experts. Women's awareness of early childhood education is still very low. Suggestions for future research to dig deeper into the causes of the role of women is still low, and influence government policy in increasing the role of Muslim women or non-Muslim women. Keywords: Role of Muslim Women, Early Childhood Education References: Britto, P. R., Lye, S. J., Proulx, K., Yousafzai, A. K., Matthews, S. G., Vaivada, T., … Bhutta, Z. A. (2017). Nurturing care: promoting early childhood development. The Lancet, 389(10064), 91–102. https://doi.org/10.1016/S0140-6736(16)31390-3 Edy, E., Ch, M., Sumantri, M. S., & Yetti, E. (2018). Pengaruh keterlibatan orang-tua dan pola asuh terhadap disiplin anak. Jurnal Pendidikan Usia Dini, 12(1). https://doi.org///doi.org/10.21009/jpud.122.03 Fauzia, S. N. (2017). Perilaku keagamaan Islam pada anak usia dini. Jurnal Pendidikan Usia Dini, 11(2). https://doi.org/://doi.org/10.21009/jpud.092.07 Frejka, T., Goldscheider, F., & Lappegård, T. (2018). The two-part gender revolution, women’s second shift and changing cohort fertility. Comparative Population Studies, 43, 99–130. https://doi.org/10.12765/CPoS-2018-09en Islamiyati, I. (2018). Hubungan kerjasama orang tua dengan perkembangan anak usia dini di kelompok bermain. Jurnal Pendidikan Usia Dini, 12(1). https://doi.org/://doi.org/10.21009//jpud.121.06 Jamhari, I. R. (2003). Citra Perempuan dalam Islam. Jakarta: Gramedia Pustaka Utama. Jum’ah, A. (2006). ). Sayyidinā Muhammad Rasulillah ila al-‘Alamin. Cairo: Dār al-Farouk. Kementrian Pendidikan dan Kebudayaan. (2013). Petunjuk Teknis Penyelenggaraan Pendidikan Anak Usia Dini. Jakarta: Direktorat Pembinaan Pendidikan Anak Usia Dini. Khan, M. Z. (2003). Woman in Islam and Her Role in Human Development. In The Muslim World. Retrieved from http://onlinelibrary.wiley.com/doi/10.1111/j.1478-1913.1914.tb01384.x/abstract Kohli, R., Lin, Y. C., Ha, N., Jose, A., & Shini, C. (2019). A way of being: Women of color educators and their ongoing commitments to critical consciousness. Teaching and Teacher Education, 82, 24–32. https://doi.org/10.1016/j.tate.2019.03.005 Mansur. (2009). Pendidikan Anak Usia Dini dalam Islam. Jakarta: Pustaka Pelajar. Masnipal. (2013). Siap Menjadi Guru dan Pengelola PAUD Professional. Jakarta: PT Elex Media Komputindo. Megawangi, R. (1996). Perkembangan Teori Feminisme Masa Kini dan Mendatang serta Kaitannya dengan Pemikiran Keislaman, dalam Man-sur Fakih, et. al. Membincang Feminisme: Diskur-sus Gender Persfektif Islam. Jakarta: Risalah Gusti. Miles, M. B., & Huberman, A. M. (1984). Qualitative Data Analysis. London: Sage Publication. Moeslichatoen. (2004). Metode Pengajaran di Taman Kanak-kanak. Jakarta: PT Rineka Cipta. Shihab, M. Q. (2001). Tafsîr al-Mishbâh. Jakarta: Lentera Hati. Siregar, N. M. (2018). Peningkatan kecerdasan interpersonal melalui aktivitas fisik anak usia 4-5 tahun. Jurnal Pendidikan Usia Dini, 12(2). https://doi.org/://doi.org/10.21009/jpud.122.10 Sujiono, Y. N. (2012). Konsep Dasar Pendidikan Anak Usia Dini. Jakarta: PT Indeks. Sumantri, M., & Syaodih, N. (2006). Perkembangan Peserta Didik. Jakarta: Universitas Terbuka. Suryana, D. (2014). Dasar-dasar Pendidikan TK. Jakarta: Universitas Terbuka. Suyadi. (2011). Pegangan Bimbingan Konseling untuk PAUD. Yogyakarta: Diva Press. Tafsir, A. (n.d.). Pendidikan Agama dalam Keluarga. Bandung: PT Remaja Rosdakarya. Yamin, M., & Sanan, J. S. (2010). Panduan Pendidikan Anak Usia Dini (PAUD). Jakarta: Gaung Persada (GP) Press. Yusmawati, & Lubis, J. (2019). The Implementation of Curriculum by Using Motion Pattern. Jurnal Pendidikan Usia Dini. https://doi.org/DOI:https://doi.org/10.21009/10.21009/JPUD.131.14